PENINGKATAN STABILITAS KURKUMIN MELALUI PEMBENTUKAN KOMPLEKS KURKUMIN-ï¢-SIKLODEKSTRIN NANOPARTIKEL DALAM BENTUK GEL - Ariani Edityaningrum, Citra; Rachmawati, Heni (Universitas Ahmad Dahlan, 2015)
Curcumin is a compound derived from turmeric. This compound is practically insoluble inwater and has poor stability. To improve the benefit of curcumin as a potential active compound in agel preparation, better stability are requested. Encapsulation was performed by freeze drying methodsand all evaluation data confirmed that curcumin included in the ï¢-cyclodextrin forming curcumin-ï¢-cyclodextrin nanoparticle. The formula showed particle size of 156.8 Â± 38.3 nm, polydispersity indexof 0.174 Â± 0.026, and zeta potential of -17.3 ï± 0.2 mV. The gelling agents used for formulation of gelbase were HPMC, CMC-Na, carbopol 940, water-soluble chitosan, and viscolam. Viscolam showedbest stability of pH and viscosity after storage at 25 and 40 oC for 28 days. The inclusion complex andcurcumin were incorporated into gel. Both of the formulas showed good stability in pH and viscosityafter storage at 25 and 40oC for 28 days, and the inclusion complex gel showed improvement in thechemical stability which is approximately 2.12-fold (p<0.01) and 1.41-fold (p<0.05), after storage at25 and 40 oC, respectively.